Work-related challenges and their associated coping mechanisms among female head porters (Kayayei) in Ghana - Komesuor, Joyce; Manu, Emmanuel; Meyer-Weitz, Anna (Frontiers in Public Health, 2024)
Background While internal migrants (Kayayei) in Ghana have been perceived as a vulnerable group facing various health-related challenges, there has not been enough research on the impact of their work on their health and well-being. This study investigated the lived experiences of the Kayayei to identify the health-related challenges associated with their work and the coping mechanisms they adopt in dealing with these challenges. Methods We interviewed 21 participants purposely selected and conducted two focus group discussions (FGD) of five participants each at the Agbogbloshie market. Interpretive Phenomenology Analysis Approach was used to identify themes and sub-themes. Statements from participants were presented as quotes to corroborate their views. Results The work-related challenges identified in the study were physical health, mental health, accommodation, and social challenges. Religion, recreation, social support, hope, resilience, and self-medication were the coping strategies adopted by the study participants. Conclusion The government of Ghana should be encouraged to work with stakeholders like social welfare to raise awareness about women’s rights, build their skills to increase their employment opportunities, enhance their safety, health, and overall well-being. It is also important to ensure the networking of relevant stakeholders to work with women in the informal sector to foster agency and provide support when needed.